2017
DOI: 10.1007/s12011-017-0994-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Mg2+ After Hemorrhagic Shock

Abstract: Hemorrhagic shock is generally characterized by hemodynamic instability with cellular hypoxia and diminishing cellular function, resulting from an imbalance between systemic oxygen delivery and consumption and redistribution of fluid and electrolytes. Magnesium (Mg) is the fourth most abundant cation overall and second most abundant intracellular cation in the body and an essential cofactor for the energy production and cellular metabolism. Data for blood total Mg (tMg; free-ionized, protein-bound, and anion-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Studies from our laboratory and others have demonstrated a significant role for mitochondria in organ dysfunction following hemorrhagic shock [5][6][7]. SIRT1, an NAD + dependent enzyme that catalyses protein deacetylation, is important in the maintenance of mitochondrial function and recent studies showed a declined activity of SIRT1 in animal models of hemorrhagic shock [4,8]. We previously reported that resveratrol and SRT1720, SIRT1 activators, improved survival following hemorrhagic shock [9].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies from our laboratory and others have demonstrated a significant role for mitochondria in organ dysfunction following hemorrhagic shock [5][6][7]. SIRT1, an NAD + dependent enzyme that catalyses protein deacetylation, is important in the maintenance of mitochondrial function and recent studies showed a declined activity of SIRT1 in animal models of hemorrhagic shock [4,8]. We previously reported that resveratrol and SRT1720, SIRT1 activators, improved survival following hemorrhagic shock [9].…”
Section: Introductionmentioning
confidence: 89%
“…Despite advances in critical care, severely injured patients still face a high degree of post-injury morbidity and mortality [2]. Hemorrhagic shock is characterized by whole body hypoxia, nutrient deprivation, hemodynamic instability and systemic inflammation, and may lead to multiple organ dysfunction and death [3,4]. Studies from our laboratory and others have demonstrated a significant role for mitochondria in organ dysfunction following hemorrhagic shock [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Магній (Mg 2+ ) є другим найбільш поширеним внутрішньоклітинним катіоном в організмі і істот-ним кофактором для виробництва енергії і клітин-ного метаболізму. У щурів ГШ викликає підвищен-ня в крові, вільного Mg 2+ і плазматичного tMg 2+ , в результаті виходу Mg 2+ з метаболічно ушкоджених клітини з ацидозом і виснаженим АТФ [9].…”
unclassified